500 bracelets : an inspiring collection of extraordinary designs - Le Van, Marthe (New York, NY Lark Books, 2005)
Never before has such a diverse collection of fine contemporary bracelets been assembled, showcasing hundreds of renowned international jewelers. Materials range from the most precious metals and gems to paper and plastic, and the varied techniques include forging, casting, weaving, and and surface embellishments. Among the featured creators: Abrasha, who contributes a Royal Pachinko Ball Bracelet; Sharon Portelance, who called her work Wrist Corsage: Ever Present; and Felieke Van Der Leest's amusingly named Hare O'Harix and His 6 Carrots. Whether you're an expert jeweler, a collector, a student, or simply someone who loves beautiful objects, these one-of-kind pieces will astound you.
Includes index
Keywords: Bracelets - Catalogs